2004
DOI: 10.1149/1.1790510
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Barrier Properties of PECVD Amorphous Silicon-Oxycarbide from Trimethylsilane and CO[sub 2]

Abstract: This work investigates the thermal stability and physical and barrier properties of amorphous silicon-carbide ͑␣-SiC͒ and amorphous silicon-oxycarbide ͑␣-SiCO͒ dielectric barriers deposited by plasma-enhanced chemical vapor deposition ͑PECVD͒ using trimethylsilane ͑3MS͒ precursor and He carrier gas. Films were deposited without and with various CO 2 flow rates. The dielectric constant of the ␣-SiCO films decreased with increasing CO 2 flow rate. Increasing CO 2 flow rate also promotes better thermal stability,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The atomic concentration of C, Si, and O is 16.6 ± 0.4%, 27.6 ± 0.2%, and 55.8 ± 0.6%, respectively. Compared to carbosiloxane films deposited using other techniques, the carbon concentration of the MLD film is within the typical range of 10–30%; it is also higher than that of films grown by inductively coupled plasma CVD (ICPCVD) using bistrimethylsilylmethane and oxygen but lower than those made by PECVD using trimethylsilane and CO 2 . To conclusively exclude the possibility of the underlying SiO 2 /Si substrate contributing to the total apparent Si signal, the MLD carbosiloxane films were also deposited on substrates precoated with 18 nm Al 2 O 3 films grown by ALD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The atomic concentration of C, Si, and O is 16.6 ± 0.4%, 27.6 ± 0.2%, and 55.8 ± 0.6%, respectively. Compared to carbosiloxane films deposited using other techniques, the carbon concentration of the MLD film is within the typical range of 10–30%; it is also higher than that of films grown by inductively coupled plasma CVD (ICPCVD) using bistrimethylsilylmethane and oxygen but lower than those made by PECVD using trimethylsilane and CO 2 . To conclusively exclude the possibility of the underlying SiO 2 /Si substrate contributing to the total apparent Si signal, the MLD carbosiloxane films were also deposited on substrates precoated with 18 nm Al 2 O 3 films grown by ALD.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to carbosiloxane films deposited using other techniques, the carbon concentration of the MLD film is within the typical range of 10−30%; 4 it is also higher than that of films grown by inductively coupled plasma CVD (ICPCVD) using bistrimethylsilylmethane and oxygen 40 but lower than those made by PECVD using trimethylsilane and CO 2 . 41 To conclusively exclude the possibility of the underlying SiO 2 /Si substrate contributing to the total apparent Si signal, the MLD carbosiloxane films were also deposited on substrates precoated with 18 nm Al 2 O 3 films grown by ALD. Figure 3b To further explore the effect of O 3 exposure time on film growth, a series of ultrathin carbosiloxane films were deposited on Al 2 O 3 -coated substrates for 100 MLD cycles using different O 3 exposure lengths.…”
Section: Resultsmentioning
confidence: 99%
“…276,277 Recent studies have also indicated that dense a-SiCO:H dielectrics can also serve as Cu diffusion barriers with k values as low as 3.5. [51][52][53]55 Given that rapid Cu diffusion through SiO 2 and low-k a-SiOC:H with k values as high ∼ 2.9 have been previously reported, 273,278,279 the break point ECS Journal of Solid State Science and Technology, 4 (1) N3029-N3047 (2015)…”
Section: N3031mentioning
confidence: 92%
“…Therefore, low-k forms of these materials were also needed to reduce the impact of the relatively high-k of PECVD a-SiN:H (k = 6.5-7.0). [41][42][43] The low-k DB/CCL/ES materials implemented to date have been primarily carbon doped silicon nitrides (a-SiNC:H) with k values of 4.5-5.8, [44][45][46][47][48][49][50][51] dense oxygen doped silicon carbides (a-SiCO:H) with k values of 4.0-4.8, [52][53][54][55][56][57][58] and pure silicon carbides (a-SiC:H) with k values of 4.0-7.0. [59][60][61][62][63][64][65][66] Similar to low-k ILDs, these materials have proven equally difficult and challenging to integrate with Cu interconnect fabrication processes.…”
mentioning
confidence: 99%
“…92,207 Since then, lower-k SiCN, SiOC, and SiC films with k as low as 4 have been demonstrated and adopted in the industry. [208][209][210][211][212][213][214] Recent experiments have also shown that high carbon content SiCH films with k as low as 3.2 may be suitable as next generation ES/DB materials. [215][216][217] However, there are scaling limits in k due to the need to maintain a dense enough material that can still function as a Cu diffusion barrier (DB) material as well as ES.…”
Section: Spacermentioning
confidence: 99%